Analysis of The Influence of Hedonic Digital Lifestyle on Consumptive E-Shopping Behavior of Generation Z Through E-Commerce Applications - Sulistyo Budi Utomo; Hisnol Jamali; Ilham Arief; M. Novan Saputra; Caka Gatot Priambodo (Jurnal Sistim Informasi dan Teknologi, 2023)
This research aims to analyze the influence of a hedonic lifestyle on consumptive behavior in purchasing clothes via e-commerce among students. The author uses a quantitative research approach as a procedural step in this research. The author uses the Estok Navitte Cowan formula to determine the sample used. For the sampling process, the author used a non-probability sampling technique. The next technique used was quota sampling, with a total of 30 students. The author uses surveys as a way to collect data and chooses questionnaires as a tool to collect the necessary data from research subjects. The Likert scale was used in this research. Researchers use Google Forms as a tool for collecting data for research. The author uses the data analysis method of recall and data categorization. Based on the research results, it shows that the hedonic lifestyle adopted by respondents is partially in the high category. Both aspects of activities, interests, and opinions related to the research object can help construct a hedonistic lifestyle. In this research, aspects were found that could construct a dominant hedonic lifestyle, such as shopping, being interested in fashion, and thinking about products. Consumer behavior in purchasing clothes in e-commerce carried out by respondents is in the high category. The types of consumer behavior in the high category are impulsive purchases and irrational purchases. These two types of consumer behavior can occur because respondents look for symbols of satisfaction and pleasure attached to clothing in e-commerce. However, the level of waste in purchasing clothes through e-commerce is low.